(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Mannitol has been used for decades for treating raised Intracranial Pressure (ICP). Recent studies reported that Hypertonic Saline (HTS) formulations are better than mannitol with a favorable safety profile. The present study’s purpose was to compare the efficacy of 20% mannitol versus 3% HTS in clinically raised ICP in patients of acute stroke managed conservatively. Materials and Method: This Randomize Controlled Trail (RCT) was conducted at the Department of Neurology, Chittagong Medical College Hospital, Chattogram from July 2021 to June 2022. Sixty-eight confirmed ischemic or hemorrhagic stroke patients with clinical signs of increased ICP and GCS 8 or below were randomly allocated to either mannitol or 3% HTS in the Chittagong Medical College Hospital, Department of Neurology. After Hyperosmolar Therapy (HT), blood pressure, Mean Arterial Pressure (MAP), heart rate, pupillary reaction, respiratory rate, and GCS were monitored for 6-48 hours. Patients’ outcomes were assessed two weeks after treatment by the Glasgow Outcome Scale (GOS) and the Modified Rankin scale (mRS) score one month later. Results: Both groups were comparable at baseline regarding demographic and clinical characteristics. SBP, DBP, and MAP reduced significantly in two groups 6 to 48 hours from baseline. The median (Interquartile range) percentage reduction of the MAP from baseline was 6.3 (3.9 to 19.2) % in the HTS group and 10 (-4.7 to 14.9) % in the Mannitol group (p=0.544). The mean GCS improved significantly from baseline values in both groups in 6, 12, 24, 36 and 48 hours. The thirty-day mortality rate was 11.8% and 38.2%, respectively, in the HTS and mannitol groups (p=0.021). In multivariate regression analysis, the patients in the mannitol group were 7.9 times (OR: 7.85, 95% CI:1.45-42.52, p=0.017) more likely to expire within 30 days than the patients in the HTS group. Conclusion: HTS could be used safely as an alternative therapy to mannitol in managing raised ICP after acute stroke. JCMCTA 2024 ; 35 (1) : 107-113